KONSEP IMPLEMENTASI PEMBELAJARAN TAFSIR AMALY DAN KAITANNYA DENGAN PEMAHAMAN AYAT TENTANG FIKIH - Qurrotul Ainiyah; Noor Fatikah; Eka Yuyun Faris Daniati (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2022)
Amaly's interpretation is a form of interpretation that does not emphasize certain studies in accordance with the specifications of interpretation as generally in the science of interpretation. However, Tafsir Amaly emphasizes more on something that can be practiced and practiced from a verse on the basis that the Qur'an was revealed by Allah SWT to be nothing but practiced in everyday life. There are several styles Tafsir , including: Hadith, Fiqh, Science and Technology, and Sufi patterns. So Amaly 's Tafsir a Sufi-style interpretation. Amaly's Tafsir does not use Arabic, but uses Indonesian, Amaly's special Tafsir Method is to use the tadabbur. This method is the same as the Amaly Tafsir in general, only the difference is in the study of each lafadz and analysis of the lafadz. In the verses about fiqh (tafsir ayata ahkam), Amaly's interpretation serves to emphasize the creed, that the shari'ah and aqidah are one unit, because every verse on law must end with the